Langston Hughes and the blues - Tracy, Steven C. (Steven Carl), 1954- (University of Illinois Press, 2024)
"The shades and structures of the blues had an immense impact on the poetry of Langston Hughes. Steven C. Tracy provides a cultural context for Hughes's work while revealing how Hughes mined Black oral and literary traditions to create his poetry. Comparing Hughes's poems to blues texts, Tracy reveals how Hughes's experimental forms reflect the poetics, structures, rhythms, and musical techniques of the music. Tracy also offers a discography of recordings by the artists--Bessie Smith, Ma Rainey, Blind Lemon Jefferson, and others--who most influenced the poet"--